Sustainability and lives of coffee farmers in Magetan Regency, East Java, Indonesia - Rahayu Endang Siti; Widadie Fanny; Irianto Heru; Handayani Sugiharti Mulya; Setyowati; Sundari Mei Tri (BIO Web of Conferences)
The lack of knowledge of farmers about efforts to manage coffee plantations with environmental and conservation views is believed to have the effects of microclimate change which are likely to impact coffee farmers in the future. The purpose of the research is to (1) identify ecological aspects on the sustainability of coffee cultivation patterns in the Magetan region, (2) find ecological factors on coffee production, and (3) describe the lives of coffee farmers related to ecological aspects. The research method was carried out by a multistage sampling method starting from the determination of subdistricts, villages, farmer groups, farmer group members, and coffee farmer samples. The data used are primary data, with a method of collecting direct survey data on 80 coffee farmers randomly in two districts of Panekan and Poncol. An analysis method to see the relationship of environmental variables to coffee production with multiple linear regression analysis and descriptive analysis for ecological aspects. he results showed that the ecological factors significantly affecting coffee production included the number of protective trees, the application of manure, and farmers' knowledge of conservation practices. Conversely, pruning and the eradication of coffee borer pests were found to have an insignificant impact. The study concludes that while efforts toward coffee sustainability have been initiated by farmers, they have not yet achieved full success. Sustainability efforts include protecting the environment through the use of manure, planting shade trees, and adopting conservation-oriented coffee cultivation practices.